MODERN PROBLEMS OF PREMATURE CHILDREN MANAGEMENT: NUTRITION - I. A. Belyayeva; G. V. Yatsyk; N. D. Odinayeva; E. O. Tarzyan ("Paediatrician" Publishers LLC, 2011)
The article presents main principles of premature infants' nutrition taking into account immature gastrointestinal system. The approaches are differentiated accordingly to gestational age and body weight. Parenteral and enteral nutrition of children with very low and extremely low body weight in early and late post-natal period is highlighted. Needs of patients in main nutritive ingredients are grounded; physiological role of several nutrients in premature infants (minerals, vitamins, essential fatty acids, nucleotides, etc.) is presented. Ready liquid nutritive mixtures are optimal for nutrition of premature patients. Two-stage system of nutrition (special mixtures for hospital management and following months of life) in extremely premature infants is described in details.